cDNAs encoding the large subunit of human replication factor C. - Bunz, F (1993)
Replication factor C (RFC) is a multisubunit, DNA polymerase accessory protein required for the coordinated synthesis of both DNA strands during simian virus 40 DNA replication in vitro. Previous studies have shown that RFC is a DNA-dependent ATPase that binds in a structure-specific manner to the 3' end of a primer hybridized to a template DNA, an activity thought intrinsic to the 140-kDa component of this multisubunit complex. Here, the isolation and analysis of cDNAs encoding this subunit is described. Analysis of the full-length coding sequence revealed an open reading frame of 3.4 kb, encoding an 1148-amino acid protein with a predicted molecular mass of 130 kDa. A putative ATP-binding motif was observed that is similar to a motif in several of the smaller subunits of RFC and in functionally homologous replication factors of bacterial and viral origin. A "DEAD" box is also conserved among these proteins. The predicted protein shows significant identity with a DNA-binding protein of murine origin (B. Luckow, P. Lichter, and G. Schütz, personal communication). Regions of similarity were also seen between the amino acid sequences of the 140-kDa subunit of RFC, poly(ADP-ribose) polymerase, and bacterial DNA ligases--possibly representing a conserved structural feature of these proteins that bind similar DNA substrates.